2020
DOI: 10.1038/s41598-019-56982-y
|View full text |Cite
|
Sign up to set email alerts
|

Melanin formation in barley grain occurs within plastids of pericarp and husk cells

Abstract: Melanins are a class of darkly pigmented biopolymers which are widely distributed among living organisms. the molecular and cellular mechanisms adopted by bacteria, fungi and animals to synthesize melanin, have been well described, but less is known regarding their production in plants. Here, a pair of barley near isogenic lines, bred to differ with respect to the pigmentation of the spike, was compared in order to understand the tissue and cellular location of melanin deposition. the melanic nature of the pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 40 publications
1
42
0
3
Order By: Relevance
“…In the study of molecular mechanisms of 'melanin-like' black seed pigments known to be strong antioxidants, comparative transcriptome analysis of two near-isogenic lines differing by the allelic state of the Blp (black lemma and pericarp) locus revealed that black seed color is related to the increased level of ferulic acid and other phenolic compounds [88]. The melanic nature of the purified black pigments was confirmed by a series of solubility tests and Fourier transform infrared spectroscopy, while intracellular pigmented structures were described to appear in chloroplast-derived plastids designated "melanoplasts" [89]. The most frequently mentioned flavonoids of cereal crops are the flavonols kaempferol and quercetin, the flavanone naringenin and its glycosylated forms, catechin, and epicatechin in barley [90][91][92][93].…”
Section: Phenolic Compounds and Avenanthramidesmentioning
confidence: 94%
“…In the study of molecular mechanisms of 'melanin-like' black seed pigments known to be strong antioxidants, comparative transcriptome analysis of two near-isogenic lines differing by the allelic state of the Blp (black lemma and pericarp) locus revealed that black seed color is related to the increased level of ferulic acid and other phenolic compounds [88]. The melanic nature of the purified black pigments was confirmed by a series of solubility tests and Fourier transform infrared spectroscopy, while intracellular pigmented structures were described to appear in chloroplast-derived plastids designated "melanoplasts" [89]. The most frequently mentioned flavonoids of cereal crops are the flavonols kaempferol and quercetin, the flavanone naringenin and its glycosylated forms, catechin, and epicatechin in barley [90][91][92][93].…”
Section: Phenolic Compounds and Avenanthramidesmentioning
confidence: 94%
“…When exposed to strong oxidizing agents, such as hydrogen peroxide, potassium permanganate, or bromine water, the pigment loses its color, while exposure to ferric chloride results in the precipitation of a flocculent material that gradually redissolves when the concentration of ferric chloride is raised. The results of the reactions indicate the presence of quinoid and phenolic groups in melanins (Thomas, 1955;Fox and Kuchnow, 1965;Lyakh, 1981;Downie et al, 2003;Shoeva et al, 2020).…”
Section: Physicochemical Methods To Identify and Study Plant Melaninsmentioning
confidence: 99%
“…Through the use of chemical tests in combination with some of the described spectroscopic techniques, the melanic nature of the black pigments in seeds has been proved for the following species: watermelon (Nicolaus et al, 1964), sunflower (Nicolaus et al, 1964;Gracheva and Zheltobryukhov, 2016), buckwheat (Zhuravel, 2010), grape (Zherebin and Litvina, 1991), tomato (Downie et al, 2003), fragrant olive (Wang et al, 2006), night jasmine (Kannan and Ganjewala, 2009), sesame (Panzella et al, 2012), ipomoea (Park, 2012), black mustard and rape (Yu, 2013), chestnut (Yao et al, 2012), garlic (Wang and Rhim, 2019), oat (Varga et al, 2016), and barley (Shoeva et al, 2020; Figure 1). Promising results in determining the structure of plant melanins were recently obtained by matrixassisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS), that was applied to resolve the structure of oat melanin, which turned out to be a homopolymer built up from p-coumaric acid and consists mainly of low molecular weight oligomers of 3-9 monomer units (Varga et al, 2016).…”
Section: Physicochemical Methods To Identify and Study Plant Melaninsmentioning
confidence: 99%
“…70‐ to 100‐µm thickness, surrounding the endosperm and germ. [ 55–57 ] Overall, lupine as well as barley seeds seemed to be more protected against detrimental effects of PPA treatment.…”
Section: Discussionmentioning
confidence: 99%